ABDULLA KAHHOR IS A LOVER AND CRITIC OF UZBEK POETRY - M. Jamoliddinov (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents a critical opinion about the Uzbek poetry of Abdulla Kakhkhor, the inner experiences and feelings of the poet during its creation, the study of ghazals created in the weight of aruz, the role of poetry in the upbringing of the younger generation.